The Influence of Brief Counseling on Work Motivation and Implementation of Patient Safety Culture in Staff at Ramdani Husada Clinic - Ika Retnani; Agusta Dian Ellina; Yenny Puspitasari (Universitas STRADA Indonesia, 2024)
The application of work motivation and patient safety culture is one facet of work culture, which is an organizational management concept. Additional evidence regarding the use and efficacy of counseling in the workplace can be obtained by understanding how different stakeholders use it. The purpose of this study is to ascertain how brief counseling affects staff members' job motivation and adoption of the Ramdani Husada Clinic's patient safety culture. Quantitative research employing a